2021
DOI: 10.1007/s10530-021-02657-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in native and introduced host–parasite networks

Abstract: Introduced species can alter the dynamics and structure of a native community. Network analysis provides a tool to study host–parasite interactions that can help to predict the possible impact of biological invasions or other disturbances. In this study, we used weighted bipartite networks to assess differences in the interaction patterns between hosts and helminth parasites of native (Sea of Japan) and invasive (Black Sea and Sea of Azov) populations of Planiliza haematocheilus (Teleostei: Mugilidae). We empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
0
9
1
Order By: Relevance
“…A network analysis showed that the invasive mullet played a peripheral role in host–parasite networks in the invaded range, compared to its native range as well as compared to another native mullet that inhabited both the invaded and native areas (Llopis-Belenguer et al , 2020). Taking these data a step further, significant differences occurred between parasite networks of the so-iuy mullet in connectedness, nestedness and modularity in the invaded and native areas (Llaberia-Robledillo et al , 2022). These network properties differed between actively-transmitted and trophically-transmitted parasites, varying not only between the parasites themselves but between invaded and native ranges (Llaberia-Robledillo et al , 2022).…”
Section: Invasive Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A network analysis showed that the invasive mullet played a peripheral role in host–parasite networks in the invaded range, compared to its native range as well as compared to another native mullet that inhabited both the invaded and native areas (Llopis-Belenguer et al , 2020). Taking these data a step further, significant differences occurred between parasite networks of the so-iuy mullet in connectedness, nestedness and modularity in the invaded and native areas (Llaberia-Robledillo et al , 2022). These network properties differed between actively-transmitted and trophically-transmitted parasites, varying not only between the parasites themselves but between invaded and native ranges (Llaberia-Robledillo et al , 2022).…”
Section: Invasive Speciesmentioning
confidence: 99%
“…Taking these data a step further, significant differences occurred between parasite networks of the so-iuy mullet in connectedness, nestedness and modularity in the invaded and native areas (Llaberia-Robledillo et al , 2022). These network properties differed between actively-transmitted and trophically-transmitted parasites, varying not only between the parasites themselves but between invaded and native ranges (Llaberia-Robledillo et al , 2022). Integrating data together at different organizational and hierarchical scales and comparing ectoparasite and endoparasite subsets between the regions in a macroecological approach, Sarabeev et al (2022) proposed fundamental differences in parasites between those co-introduced and those acquired in an invaded range that include abundance–variance and abundance–occupancy relationships, core-satellite species, patterns of aggregation and prevalence frequency distributions, infrapopulation size, and infracommunity species richness.…”
Section: Invasive Speciesmentioning
confidence: 99%
“…The proposed framework can be used to assess how invasive hosts integrate new ecosystems. In this regard, we think that network analysis of the host-parasite system opens an avenue of further research, providing a tool to study host-parasite interactions and to predict the possible impact of biological invasions on ecosystems (Llopis-Belenguer, Blasco-Costa, et al, 2020;Llaberia-Robledillo et al, 2021). Despite these encouraging findings, the current study is limited to a single invasive host and encompassing ectoparasitic and endoparasitic subsets of species.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 96%
“…Moreover, by considering parasite subsets according to transmission mode, we can obtain additional insights into understanding host-parasite relationships of invasive hosts (e.g. Llopis-Belenguer et al 2020a;Llaberia-Robledillo et al 2021). The key objective of both the researchers and stakeholders is a search for effective and safe methods to control invasive species in an ecosystem, while the framework described here can be used as a tool to assess the suppressive effect of parasites on host populations.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Pankov [ 69 ] assessed diversity indices of helminths in four species of the family Mugilidae from Bulgarian waters of the Black Sea. A number of papers analyzed parasite communities in the grey mullet Mugil cephalus and the invasive redlip mullet Planiliza haematocheilus [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Introductionmentioning
confidence: 99%